Localized cortical injections of ethosuximide suppress spike-and-wave activity and reduce the resistance to kindling in genetic absence epilepsy rats (GAERS) - ONAT, FİLİZ; GÜLHAN, REZZAN (ELSEVIER, 2010)
Models of genetic absence epilepsy are resistant to secondary generalization of focal limbic seizures. This correlates with the postnatal development of spike-and-wave discharges (SWDs), a hallmark of absence seizures arising from a cortical focus in the perioral region of somatosensory cortex. Ethosuximide injected at this site suppresses SWDs. The effect of this suppression on kindling in Genetic Absence Epilepsy Rats from Strasbourg (GAERS), has been compared for postnatal 30 day (PN30) rats having immature SWDs and adult (>4 months) rats having mature SWDs. Non-epileptic Wistar and GAERS rats were implanted with a basolateral amygdaloid stimulation electrode, bilateral injection cannulas into the cortical perioral focus, and cortical recording electrodes. Following recovery cortical injections of ethosuximide or saline were made and after 30 min rats were given 36 stimulations or until Racine's stage 5 seizures were produced. All Wistar rats (PN30 and adult) treated with saline or ethosuximide reached stage 5. Of GAERS given saline, 33% (PN30) and 43% (adults) were resistant to kindling; after ethosuximide pups behaved like Wistars, but adults showed a delay in kindling relative to Wistars. These findings imply that mechanisms underlying kindling resistance are related but not limited to SWD activity in animals with genetic absence epilepsy. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cortical focus; Limbic epilepsy; Circuitry; Amygdala; Temporal lobe; SWD; IDIOPATHIC GENERALIZED EPILEPSY; TEMPORAL-LOBE; THALAMIC NUCLEI; SEIZURES; MODEL; COEXISTENCE; DISCHARGES; MECHANISMS; EXPRESSION; NEURONS